2021
DOI: 10.3233/tub-211506
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer suppression by curcumin-naringenin-magnetic-nano-particles: In vitro and in vivo studies

Abstract: BACKGROUND: The limitations of surgery, radiotherapy, and chemotherapy in cancer treatment and the increase in the application of nanomaterials in the field of biomedicine have promoted the use of nanomaterials in combination with radiotherapy for cancer treatment. OBJECTIVE: To improve the efficiency of cancer treatment, curcumin-naringenin loaded dextran-coated magnetic nanoparticles (CUR-NAR-D-MNPs) were used as chemotherapy and in combination with radiotherapy to verify their effectiveness in treating tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…However, cells incubated with CUR-NAR-D-MNPs 48 h before radiotherapy had exacerbated apoptosis and necrosis percentages compared to those that received radiotherapy, indicating this compound’s antiproliferative and radiosensitizing activity. When evaluating the effect of CUR-NAR-D-MNPs in female Sprague Dawley rats, the treatment reduced tumor volume, leading to cell cycle arrest and induction of apoptosis through modulation of signaling, high p53, high p21, low TNF-α, low CD44, and high RS [ 161 ].…”
Section: Naringenin and Hesperidin: An Overviewmentioning
confidence: 99%
“…However, cells incubated with CUR-NAR-D-MNPs 48 h before radiotherapy had exacerbated apoptosis and necrosis percentages compared to those that received radiotherapy, indicating this compound’s antiproliferative and radiosensitizing activity. When evaluating the effect of CUR-NAR-D-MNPs in female Sprague Dawley rats, the treatment reduced tumor volume, leading to cell cycle arrest and induction of apoptosis through modulation of signaling, high p53, high p21, low TNF-α, low CD44, and high RS [ 161 ].…”
Section: Naringenin and Hesperidin: An Overviewmentioning
confidence: 99%
“…Moreover, curcumin combined with naringenin loaded dextran-coated magnetic nanoparticles (Cur-Nar-D-MNPs) inhibited cell proliferation and induced apoptosis through ROS production, increased P53 and P21, and decreased TNFα and CD44 in MCF-7 human breast cancer cells. Furthermore, CUR-NAR-D-MNPs reduced the tumor volume and caused the cell cycle arrest in DMBA-induced mammary tumor in rats ( Askar et al, 2021 ). Additionally, GANT61, a hexahydro pyrimidine derivative, can target CSCs of different types of human cancers through the GLI1 protein of the Hedgehog pathway.…”
Section: Tumor Cells Targeting By Nanoparticlesmentioning
confidence: 99%
“…In addition, magnetic nanoparticles (MNPs) exhibit strong antioxidant activity and free radical-scavenging properties, due to electron transfer from the Fe +2 /Fe +3 systems of iron oxide nanoparticles [ 93 ]. In the work by Askar et al, in 2021 two natural polyphenols curcumin and NAR were loaded in dextran-coated magnetic nanoparticles (CUR-NAR-D-MNPs) and used as a radiosensitizer and chemotherapeutic agent to improve the effectiveness of curcumin-NAR in treating tumors [ 94 ]. Dextran is a water-soluble polysaccharide that can decrease the saturation magnetization of magnetic nanoparticles, thereby decreasing their cytotoxicity and increasing their biocompatibility [ 95 ].…”
Section: Nar Nanoformulations With Anti-oxidative Stress Properties A...mentioning
confidence: 99%
“…This formulation is speculated to improve the cellular uptake and thereby higher accumulation of nanoparticles (NPs) inside the cancer cell. Further experiments revealed that oral administration of CUR-NAR-D-MNPs to breast cancer-bearing rats was associated with reduced tumor volume and cell cycle arrest possibly through modulation of P53high, P21high, TNF-low, CD44low, and ROS-high signaling [ 94 ].…”
Section: Nar Nanoformulations With Anti-oxidative Stress Properties A...mentioning
confidence: 99%